Effect of gamma irradiation and modified atmosphere packaging on postharvest behavior of dragon fruit - Saran, F Y; Hassan, M K; Akhther, N (Bangladesh Journal of Nuclear Agriculture, 2025)
The experiment was conducted at the Postharvest Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period of September to October, 2022 to find the effects of gamma irradiation and modified atmosphere packaging on postharvest behavior of dragon fruit. The experiment was laid out in completely randomized design with three replications. There were four treatments, viz. T0: Control, T1: gamma irradiation at 1000 Gy, T2: 1000 Gy irradiated fruits wrapped in non-perforated PP bag (25μ) containing KMnO4, T3: 1000 Gy gamma irradiated fruits wrapped in 25μ perforated PP bag containing KMnO4. Data were recorded on weight loss, firmness, color, flavor, shrinkage, freshness, appearance, total doluble sugar (TSS), diseases severity and shelf life at different days after storage. The longest shelf life (7.7 days) was recorded in 1000 Gy irradiated fruits and the shortest shelf life (5.3 days) was found in untreated control. .The minimum weight loss (0.01%) was found in 1000 Gy gamma irradiated fruits wrapped in non-perforated PP bag containing KMnO4 and maximum weight loss (3.44%) in untreated control at 7th day after storage. The findings would greatly contribute in reducing postharvest loss of dragon fruit and maintain their quality during storage and marketing at ambient condition. Bangladesh J. Nuclear Agric, 38(2): 1-13, 2024